Prioritization, Development, and Validation of American Association of Cardiovascular and Pulmonary Rehabilitation Performance Measures. Issue 4 (July 2018) - Pack, Quinn R.; Bauldoff, Gerene; Lichtman, Steven W.; Buckley, Maria; Eichenauer, Kent; Gavic, Anne; Garvey, Chris; King, Marjorie L.
Abstract : Background: In 2014, the American Association of Cardiovascular and Pulmonary Rehabilitation Quality of Care Committee was asked to develop performance measures (PMs) to assess program quality and aid in program improvement and certification. Methods: A 3-step process was used to prioritize, develop, and then validate new PMs for both cardiac and pulmonary rehabilitation programs. First, we surveyed national leadership, medical directors, and program directors to identify and rank various American Association of Cardiovascular and Pulmonary Rehabilitation potential PM topics. Then, the face validity of the drafted PMs was assessed in a second national survey. Finally, we assessed the inter- and intrarater reliability and feasibility of each PM by abstracting patient charts at programs throughout the United States. At each step, modifications were made to refine and improve the measures for clarity, reliability, and consistency. Results: Through survey answers received from 302 people (19% response rate), we identified 5 categories for PM development: optimal blood pressure control, tobacco use cessation, and improvement in functional capacity, depression, and sensation of dyspnea. After drafting the PMs, a second survey with 82 respondents (57% response rate), found that the proposed PMs had good face validity. Finally, we found excellent inter- and intrarater reliability for the blood pressure, functional capacity, depression, and dyspnea measures (κ generally >0.80.) However, validity concerns were raised about the tobacco intervention PM as written, and it continues to undergo further refinement and testing. Conclusions: We developed and validated 5 new PMs for use in cardiac and pulmonary rehabilitation program quality assessment, improvement, and certification. Abstract : Supplemental Digital Content is Available in the Text.Through 2 national surveys and 1225 patient chart abstractions, the Quality of Care Committee of the American Association of Cardiovascular and Pulmonary Rehabilitation identified, developed, and validated 5 new performance measures for use in cardiac and pulmonary rehabilitation to aid in program evaluation and quality improvement.